Implementasi Kebijakan Jaringan Gas Bumi Untuk Rumah Tangga Di Kecamatan Limapuluh Kota Pekanbaru - Ricky Wijaya Kusuma; Hasim As’ari (Jurnal Penelitian Administrasi Publik, 2021)
The scarcity of fuel in the community has prompted the Pekanbaru City Government to hasten the Natural Gas program for households by the Ministry of Energy and Mineral Resources (Energy and Mineral Resources). Pekanbaru City until 2020 already has 12,473 House Connections with PT. Civil Energy Development Facility as program operator. Limapuluh District is the first area to receive the Program with 3713 House Connections. The purpose of this study is to provide a description and analysis of the implementation of the program as well as to identify the factors that hinder the implementation of the program for household activities. The results of this study are shown based on the variables of policy implementation according to Charles O. Jones, namely Organization, Interpretation and Application. Based on these three variables, the implementation of the Natural Gas Distribution program has been going well, although there are still problems found including the limited number of Human Resources in the implementing organization to the number of natural gas connections in Pekanbaru City, the lack of communication between the program implementers and the community, so there are still people who do not want to receive the program or have not been able to enjoy the Natural Gas program, and there are still technical problems in the operation of the program. Keywords: Implementation, Policy, Natural GasNetwork